Exploration of Digital Teaching Faced by Teachers in the Pandemic Era - Chu, Li-Chuan; Lee, Yi-Te (Archives of Business Research, 2024)
The COVID-19 pandemic has prompted a significant shift to remote work and distance learning, requiring individuals to adapt to new technologies. This study analyzed data from 2,500 junior high school teachers in Chaiyi, Taiwan, revealing that high system service quality positively impacts teaching competencies, teacher involvement, and effectiveness. Despite advancements in digital tools, challenges such as equipment availability and varying teacher willingness hinder widespread adoption. Effective remote teaching requires ongoing support from institutions and the enhancement of teachers' digital literacy to ensure optimal learning outcomes.